(untitled) (CIPEEX, 2025)
INTRODUCTION: Although great advances have been made in the discovery of plant-based antimicrobials, research involving the investigation of the pharmaceutical properties of regional products is still very scarce, especially with regard to the antibacterial potential of Justicia nodicaulis. METHODOLOGY: Thus, considering the ethnopharmacological use of this plant species for the treatment of respiratory tract diseases, given that bacteria, together with viruses, are the etiological agents of many respiratory diseases, we sought to investigate the antibacterial activity of the essential oil extracted from the aerial parts of this medicinal species through broth microdilution tests performed according to the recommendations of the Clinical and Laboratory Standard Institute (CLSI), with modifications, against gram-positive and gram-negative microorganisms from four American Type Culture Collection (ATCC) standard strains. RESULTS: The results of this study demonstrated that the bactericidal activity of the essential oil obtained from J. nodicaulis was satisfactory, since, although one strain of Escherichia coli showed resistance, the oil had weak antibacterial action against Pseudomonas aeroginosa and moderate antibacterial activity against strains of Staphylococcus aureus and S. epidermidis. CONCLUSION: Although preliminary, this study may open up new paths for the development of an effective herbal medicine for the treatment of infectious diseases.